2016
DOI: 10.1080/10691898.2016.1207404
|View full text |Cite
|
Sign up to set email alerts
|

Markov Processes: Exploring the Use of Dynamic Visualizations to Enhance Student Understanding

Abstract: Finding ways to enhance introductory students' understanding of probability ideas and theory is a goal of many first-year probability courses. In this article, we explore the potential of a prototype tool for Markov processes using dynamic visualizations to develop in students a deeper understanding of the equilibrium and hitting times distributions. From the literature and interviews with practitioners, we identified core probability concepts, problematic areas, and possible solutions from which we developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…TinkerPlots, as shown in the study conducted by Biehler et al (2018) and Frischemeier and Schnell (2021) is a robust software tool that uses dynamic visualisations to facilitate students' engagement with the modelling process such as that of experienced practitioners in the field. Pfannkuch and Budgett (2016) also acknowledged the resemblance between TinkerPlots and statistical modelling practice. They observed that mathematical models are constructed using mathematical equations as fundamental building blocks.…”
Section: Discussionmentioning
confidence: 99%
“…TinkerPlots, as shown in the study conducted by Biehler et al (2018) and Frischemeier and Schnell (2021) is a robust software tool that uses dynamic visualisations to facilitate students' engagement with the modelling process such as that of experienced practitioners in the field. Pfannkuch and Budgett (2016) also acknowledged the resemblance between TinkerPlots and statistical modelling practice. They observed that mathematical models are constructed using mathematical equations as fundamental building blocks.…”
Section: Discussionmentioning
confidence: 99%
“…The Markov Chains tool (https://www.stat.auckland.ac.nz/~wild/MarkovChains/) is a dynamic visual representation of a Markov chain (Pfannkuch & Budgett, 2016). Probabilities are entered into a transition matrix, which results in the creation of a state diagram (Figure 1).…”
Section: The Markov Chains Toolmentioning
confidence: 99%
“…Research has also been devoted to students' statistical and probabilistic thinking, statistical reasoning, and communication skills (Dunn et al, 2016;Gordon & Finch, 2010;Malaspina & Malaspina, 2020;Pfannkuch, 2011;Pfannkuch & Wild, 2004). Tremendous efforts were put into enhancing statistics teaching and learning through various pedagogical approaches and technology (e.g., Pfannkuch & Budgett, 2016;Wild et al, 2015).…”
Section: Introductionmentioning
confidence: 99%